Assessment of Severity of Anemia Among Children Under 5 Years - obaid, Khamees; Ma’ala, Eqbal (Iraqi National Journal of Nursing Specialties, 2013)
Objective(s): The aim of this study was to assess the severity of anemia among children under 5 years and to findout relationship between severity of anemia in children with socio-demographic variables such as: child gender,age, supplement diet, hookworm, pica, parent's education level, father's and mother's occupation, and familymonthly income with severity of anemiaMethodology: A descriptive cross sectional study was conducted at the primary health care centers in Alsadr cityfor the period of 1st July 2011 to the 1st November 2011.Non probability (purposive) sample of (630) children whoaged under 5 years and who attended to primary health care centers of Alsadr city. The data were collectedthrough using special constructed questionnaire designed, which comprises two parts. Part one consists of child'sdemographic characteristics and their families filled by using interview technique and part of two consisthemoglobin level. The reliability of the questionnaire was determined through a pilot study and the validitythrough a panel of experts. The data were analyzed through the application of descriptive statistic frequency,percentage, and the application of inferential statistical procedures, which multiple logistic regressionsResults: The results of the study indicated that (69%) of children have anemia in general, and (35%) of them havemoderate anemia, (31%) of them have mild anemia and (3%) of them have severe anemia. The results of the studyindicated there is significant relationship between severity of anemia with supplement diet, pica, mother'seducation and family monthly income. Moreover, there is no significant association between severity of anemia inchildren and (child's gender, child's age, infection worms, father's education level, parents' occupation.Recommendations: The researchers recommend the application of screening program for anemia and determinethe severity of anemia, especially children under 5 years and increase community awareness about the dangers ofanemia especially sever of anemia in children